Powerpoint 2003 In Easy Steps
PowerPoint 2003 in easy steps covers all the essential features of the latest version of Microsoft s leading presentation software. If you want affordable, detailed, practical information with lots of helpful, full-color illustrations all organized in a concise, easy to understand format then this is the book for you! PowerPoint 2003 in easy steps uses a step by step approach that ensures you learn at your own pace. The first chapter takes you through the basics of the PowerPoint screen and its various views then shows you how to create your first slide show. Later chapters explain advanced techniques in a friendly, informative way, using plenty of walkthroughs.